The strategy of Science Learning in Curriculum 2013 to Increase the Value of Science’s Program for International Student Assessment (PISA) - Hartono Hartono; Ratu Ilma Indra Putri; Rita Inderawati; Melly Ariska (Jurnal Penelitian Pendidikan IPA, 2022)
Natural Science subjects consisting of Physics, Chemistry and Biology are given to all students starting from elementary school to equip students with logical, analytical, systematic, critical, and creative thinking skills, as well as the ability to work together. According to the Organization for Economics Cooperation and Development (OECD) in 2013, the conception of Science literacy in the PISA (Program for International Student Assessment) supports the importance of students developing a solid understanding of the concepts of pure science and science education and the benefits involved in exploration in the abstract world that exists. on the universe. This study resulted in an analysis of science learning strategies for students of the Department of Science Education that support higher order thinking skills in Science. Two (2) parts of the material will be discussed more focused, namely (a) learning materials and (b) learning strategies. With the learning syllabus that supports the High Order Thinking Skills (HOTS) questions, the opportunity to increase the value of Science education (Physics, Chemistry, Biology) is greater, one of which is the preparation of challenging questions. Challenging science questions will meet the criteria for high-level questions (PISA has question levels from level 1 to level 6). HOTS questions support the development of a solid understanding of pure Science and Science Education concepts. The data sources used in the preparation of this research are the results of the 2000, 2003, 2006, 2009, 2012, 2015 and 2018. PISA surveys and the 2013 curriculum book sourced from the Ministry of Education and Culture.